Caffenol-C: a viable alternative to conventional radiographic developer - Sudhakar, Sankaran; Shreenivas, Sundar; Rajkumar, Couppoussamy; Jones , Sumathi (International Journal Of Community Medicine And Public Health, 2024)
Current radiographic developers are considered detrimental and hence there is a constant quest for less harmful products. Caffenol-C a liquid concoction of household materials is considered as an alternative photographic developing agent. However, its usage in radiology has not been evaluated. Considering this, the present work was conducted to assess the utility of caffenol-C in processing dental radiographs. 2.6 g of instant coffee and vitamin C powder is mixed in 22.5 ml of water. Then 1.6 g of washing soda is dissolved in another 22.5 ml of water. Both the solutions are then mixed to make the final caffenol-C preparation. The preparation is then used for processing of dental radiographs and evaluated for its diagnostic quality. Radiographs developed with caffenol-C preparation showed excellent contrast and density. The optimum developing time was found to be 10 min. The present work observed that the radiographs processed with caffenol-C preparation had good diagnostic quality and thus it appears to be a viable alternative.